Modeling features of field line resonance observable by a single spacecraft at Saturn - Elsden,T; Southwood,DJ (JGR: Space Physics, 2023)
The observations of Southwood et al. (2021, https://doi.org/10.1029/2020JA028473), using data from the Cassini magnetometer from the final (proximal) orbits of the mission at Saturn, show large scale azimuthally polarized magnetic signals are always present near periapsis. The signals were attributed to standing Alfvén waves excited on the magnetic shells planetward of the Saturn D-ring. The apparent absence of any systematic variation in frequency as the spacecraft crossed magnetic shells, implied that the signals were not simply locally excited standing Alfvén modes, but were pumped by coupling to global compressional eigenmodes excited in a cavity formed in the dayside magnetosphere. In this study, we use a numerical magnetohydrodynamic (MHD) model to test such theoretical explanations for the observations, by examining in detail the MHD wave coupling and large scale spatial structure of the signals. The modeling not only shows good agreement with the data but further provides new insight into features previously overlooked in the data. In particular, we show how the apparent frequency of a single spacecraft observation is affected by the phase variation present in a local field line resonance.